Fabrication and Characterization of Epitaxial Gd‐Doped SBN Thin Films. Issue 8 (28th December 2018) - Lam, Ka Kin; Chan, Ka Ho; Ng, Sheung Mei; Wong, Hon Fai; Liu, Yu Kuai; Leung, Chi Wah; Mak, Chee Leung
Abstract : Gd‐doped Sr0.5 Ba0.5 Nb2 O6 (SBN50) thin films with Gd‐doping concentration ranging from 1 to 4% are grown on Pt‐coated MgO (100) substrates using pulsed laser deposition technique. X‐ray diffraction studies show that the films are highly (001)‐oriented and epitaxially grown on the substrates. Electrical measurements show that the Gd‐SBN films possess good ferroelectric properties. Ramanent polarization of +P r  = 1.36 μC cm −2 and −P r  = −5.73 μC cm −2 and coercive field of +E c   = 158.0 kV and −E c   = −30.8 kV are obtained. Abstract : Gd‐doped Sr0.5 Ba0.5 Nb2 O6 thin films are grown on Pt‐coated MgO (100) substrates using pulsed laser deposition technique. X‐ray diffraction studies show that the films are highly (001)‐oriented and epitaxially grown on the substrates. Ramanent polarization of + P r  = 1.36 µC cm −2 and − P r  = −5.73 µC cm −2 and coercive field of + E c  = 158.0 kV and − E c  = −30.8 kV are obtained.